2009
DOI: 10.1097/nmd.0b013e3181963ede
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning in Life for Hospitalized Patients With Schizophrenia

Abstract: This study investigated the relationship between the sense of meaning in life, quality of life, medical adherence, and duration of hospitalization among 60 inpatients at the Lev Hasharon Medical Center in Israel. Participants included men and women diagnosed with schizophrenia, whose psychiatric histories dated back at least 5 years. Participants were administered the following self-report questionnaires: Purpose In Life (Crumbaugh and Maholick, 1968), Condensed Quality of Life Enjoyment and Satisfaction (Rits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…They had hypothesized that there would be a significant negative relationship between presence of meaning and symptom levels and a positive relationship between search and symptom levels. Similar results have been reported among 49 patients hospitalized with schizophrenia (Stolovy et al, 2009) and among 171 older adults reporting depressive symptoms (Westerhof et al, 2010). Pesut, Clark, Maxwell, and Michalak (2011) conducted a literature review concerning spirituality and BIPO in which they found only six articles.…”
Section: Depressive Disordersupporting
confidence: 70%
See 2 more Smart Citations
“…They had hypothesized that there would be a significant negative relationship between presence of meaning and symptom levels and a positive relationship between search and symptom levels. Similar results have been reported among 49 patients hospitalized with schizophrenia (Stolovy et al, 2009) and among 171 older adults reporting depressive symptoms (Westerhof et al, 2010). Pesut, Clark, Maxwell, and Michalak (2011) conducted a literature review concerning spirituality and BIPO in which they found only six articles.…”
Section: Depressive Disordersupporting
confidence: 70%
“…There are only a few studies examining the impact of spirituality and meaning in life on depressive symptoms (Mascaro & Rosen, 2008;Schnetzer et al, 2013;Stolovy et al, 2009;Westerhof et al, 2010), all of which reported a negative relationship between these factors and depressive symptomatology. For example, Mascaro and Rosen (2008) found among a sample of 395 undergraduate students that there was a small but significant inverse relationship between the baseline reported level of existential meaning and depressive symptoms 2 months later.…”
Section: Depressive Disordermentioning
confidence: 97%
See 1 more Smart Citation
“…The inability to find meaning in life after encountering adverse situations can result in extreme distress (45). Studies show that individuals with SMI are capable of searching for and finding meaning (11, 52). For example, Piltch (53) described her recovery process from major depression, in which finding meaningful roles and activities (i.e., parenthood and acquiring a profession), was facilitative not only of recovery, but also had elements that can otherwise be described as PTG.…”
Section: Introductionmentioning
confidence: 99%
“…The studies that have investigated the relationship of meaning in life with psychological well-being and depression are relatively few, and in general they demonstrate significant negative relationships among these variables. However, they have been conducted in the United States of America and with specific populations such as individuals with multiple sclerosis (Hart, Fonareva, Merluzzi, & Mohr, 2005), HIV (Lyon & Younger, 2001), cancer (Simonelli, Fowler, Maxwell, & An-dersen, 2008), Schizophrenia (Stolovy, Lev-Wiesel, Adiel, & Gelkopf, 2009), older adults (Westerhof et al, 2010) and college students (Mascaro & Rosen, 2005Robak & Griffin, 2000). The need for further investigation of the relationship of meaning in life with depression and psychological well-being in other populations and in other sociocultural environments, such as the European one and more specifically the one of Greece, is necessary and becomes even more important, if we consider that depression is closely connected with suicidal ideation and mortality, which seem to be mediated by the concept of hopelessness.…”
Section: Introductionmentioning
confidence: 99%